2019
DOI: 10.1002/cctc.201901465
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Amidation without an External Hydrogen Source Using Rhodium on Carbon Matrix as a Catalyst

Abstract: An efficient method for preparation of secondary amides from primary amides and aldehydes using rhodium on carbon matrix as catalyst was developed. The method does not require any external hydrogen source and carbon monoxide is used as a reducing agent. The most active rhodium catalysts were characterized by BET, TEM and XPS techniques. Unexpectedly, it was found that heterogeneous rhodium on carbon matrix works as precatalyst for homogenous active species due to leaching of rhodium to the solution. Various se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…First, we studied the reaction of 4-nitrophenol with acetic acid in the presence of converter gas to produce paracetamol (3a). In accordance with previous reports on related processes, 7,[16][17][18][19] we found that ruthenium complexes are efficient catalysts for this transformation. Under optimal conditions, the commercially available ruthenium catalyst [(cymene)RuCl 2 ] 2 (at 1 mol% loading) allowed us to obtain paracetamol (3a) in 99% yield (Table 1, entry 1).…”
Section: Resultssupporting
confidence: 93%
“…First, we studied the reaction of 4-nitrophenol with acetic acid in the presence of converter gas to produce paracetamol (3a). In accordance with previous reports on related processes, 7,[16][17][18][19] we found that ruthenium complexes are efficient catalysts for this transformation. Under optimal conditions, the commercially available ruthenium catalyst [(cymene)RuCl 2 ] 2 (at 1 mol% loading) allowed us to obtain paracetamol (3a) in 99% yield (Table 1, entry 1).…”
Section: Resultssupporting
confidence: 93%
“…46 Thus, the chemoselective synthesis of amides is one of the most important transformations. 47 The OA of aldehydes and alcohols has been realized in the past using noble metal catalysts, such as Ag, 48,49 Au, 50 Pd, 51 Rh, 52 and Ru. 53 In parallel, several examples of efficient, less expensive catalysts such as FeCl 2 ·4H 2 O, 54 ZnI 2 , 55 TBAI, 56 I 2 , 57 and Cu I -catalysts are found.…”
Section: Introductionmentioning
confidence: 99%
“…All these facts result in a huge demand for efficient approaches towards amide bond formation in the pharmaceutical industry. 5–13…”
mentioning
confidence: 99%
“…All these facts result in a huge demand for efficient approaches towards amide bond formation in the pharmaceutical industry. [5][6][7][8][9][10][11][12][13] One of the possible ways to overcome these problems is using nitroarenes as a nitrogen source and coupling them with carboxylic acids without activators. Nitroarenes are stable and cheap reagents.…”
mentioning
confidence: 99%